2020
DOI: 10.1111/ele.13458
|View full text |Cite
|
Sign up to set email alerts
|

Social immunity modulates competition between coinfecting pathogens

Abstract: Coinfections with multiple pathogens can result in complex within-host dynamics affecting virulence and transmission. While multiple infections are intensively studied in solitary hosts, it is so far unresolved how social host interactions interfere with pathogen competition, and if this depends on coinfection diversity. We studied how the collective disease defences of antstheir social immunityinfluence pathogen competition in coinfections of same or different fungal pathogen species. Social immunity reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 97 publications
(142 reference statements)
0
14
0
Order By: Relevance
“…It was assumed that host immunity was first inhibited by Metarhizium , which led to the mycosis of insects by the fast-growing saprophytes [ 54 , 55 ]. The coinfection of ants with different Metarhizium strains and species (i.e., M. robertsii and M. brunneum ) revealed that insect social immunity (sanitary care by grooming to reduce spore load) also affect the consequence of parasite competitions [ 56 ]. Thus, the host effect on competition can be species-dependent, which requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…It was assumed that host immunity was first inhibited by Metarhizium , which led to the mycosis of insects by the fast-growing saprophytes [ 54 , 55 ]. The coinfection of ants with different Metarhizium strains and species (i.e., M. robertsii and M. brunneum ) revealed that insect social immunity (sanitary care by grooming to reduce spore load) also affect the consequence of parasite competitions [ 56 ]. Thus, the host effect on competition can be species-dependent, which requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, this may confer improved tolerance to infections where the impact it has on the host is ameliorated, e.g., through increased food consumption (Almberg et al, 2015), leading eventually to reduced pathogen virulence. Pathogen evolution and diversity could be altered by simple social behaviors, such as grooming, leading to disrupted within-host pathogen dynamics during coinfections that result in altered pathogen communities and virulence (Milutinović et al, 2020). This could select for group-living if it positively affects host fitness.…”
Section: Group Formationmentioning
confidence: 99%
“…We found that only the individual lines under current individual ant conditions caused high host mortality (Fig. 2a; Bayesian Multi Level Model, 0.44 mean probability of dying, highest density interval individual, so that strains that are outcompeted in individual hosts can in some cases gain competitive advantage in social hosts 24 . By biasing the competitive outcome of pathogen-pathogen interactions, social immunity thus exerts a modulatory effect on co-infecting pathogens.…”
Section: Social Immunity Lowers Virulence and Boosts Spore Productionmentioning
confidence: 89%
“…To experimentally assess the long-term selective effect of social immunity on co-infecting pathogens, we performed a serial passage experiment using six representatives of a natural population of pathogenic Metarhizium fungi 24,27 and the invasive Argentine ant, Linepithema humile. We subjected the ants to two different selection treatments, one excluding social immunity by keeping exposed ants individually, and the other with social immunity provided by two caregiving nestmates.…”
Section: Social Immunity Lowers Virulence and Boosts Spore Productionmentioning
confidence: 99%
See 1 more Smart Citation